Adipocyte Gs but not Gi signaling regulates whole-body glucose homeostasis - Alexandre Caron; Ryan P. Reynolds; Carlos M. Castorena; Natalie J. Michael; Charlotte E. Lee; Syann Lee; Rebecca Berdeaux; Philipp E. Scherer; Joel K. Elmquist (Elsevier, 2019)
Objective: The sympathetic nervous system (SNS) is a key regulator of the metabolic and endocrine functions of adipose tissue. Increased SNS outflow promotes fat mobilization, stimulates non-shivering thermogenesis, promotes browning, and inhibits leptin production. Most of these effects are attributed to norepinephrine activation of the Gs-coupled beta adrenergic receptors located on the surface of the adipocytes. Evidence suggests that other adrenergic receptor subtypes, including the Gi-coupled alpha 2 adrenergic receptors might also mediate the SNS effects on adipose tissue. However, the impact of acute stimulation of adipocyte Gs and Gi has never been reported. Methods: We harness the power of chemogenetics to develop unique mouse models allowing the specific and spatiotemporal stimulation of adipose tissue Gi and Gs signaling. We evaluated the impact of chemogenetic stimulation of these pathways on glucose homeostasis, lipolysis, leptin production, and gene expression. Results: Stimulation of Gs signaling in adipocytes induced rapid and sustained hypoglycemia. These hypoglycemic effects were secondary to increased insulin release, likely consequent to increased lipolysis. Notably, we also observed differences in gene regulation and ex vivo lipolysis in different adipose depots. In contrast, acute stimulation of Gi signaling in adipose tissue did not affect glucose metabolism or lipolysis, but regulated leptin production. Conclusion: Our data highlight the significance of adipose Gs signaling in regulating systemic glucose homeostasis. We also found previously unappreciated heterogeneity across adipose depots following acute stimulation. Together, these results highlight the complex interactions of GPCR signaling in adipose tissue and demonstrate the usefulness of chemogenetic technology to better understand adipocyte function. Keywords: Adipose tissue, DREADD, Glucose, Insulin, Leptin, Lipolysis